Reactome pathway analysis from whole-blood transcriptome reveals unique characteristics of systemic sclerosis patients at the preclinical stage - Bellocchi, Chiara; Wang, Xuan; Lyons, Marka A.; Marchini, Maurizio; Lorini, Maurizio; Carbonelli, Vincenzo; Montano, Nicola; Assassi, Shervin; Beretta, Lorenzo (Frontiers in Immunology, 2023)
Objective: To characterize differential expressed pathways (DEP) in subjects with preclinical systemic sclerosis (PreSSc) characterized uniquely by Raynaud phenomenon, specific autoantibodies and/or capillaroscopy positive for scleroderma pattern. Methods: Whole blood samples from 33 PreSSc with clinical prospective data (baseline and after 4 years of follow-up) and 16 matched healthy controls (HC) were analyzed for global gene expression transcriptome analysis via RNA sequencing. Functional Analysis of Individual Microarray Expression (FAIME) method annotated Reactome individualized pathways. ANOVA analysis identified DEP whose predictive capability were tested in logistic regression models after extensive internal validation. Results: At 4 years, 42.4% subjects progressed (evolving PreSSc) while the others kept stable PreSSc clinical features (stable PreSSc). At baseline, out of 831 pathways, 541 DEP were significant at a FDR<0.05 differentiating PreSSc versus HC with an AUROC=0.792±0.242 in regression models. Four clinical groups were identified via unsupervised clustering (HC; HC and PreSSc with HC-like features; PreSSc and HC with PreSSc-like features; PreSSc). Biological signatures changed with disease progression while remained unchanged in stable subjects; the magnitude of change was related to the baseline cluster, yet no DEP at baseline was predictive of progression. Disease progression was mostly related to changes in signal transduction pathways, especially linked to calcium-related events and inositol 1,4,5-triphosphate metabolism. Conclusions: PreSSc had distinguished Reactome pathways signatures compared to HC. Progression to definite SSc was characterized by a shift in biological fingertips. Calcium-related events promoting endothelial damage and vasculopathy may be relevant to disease progression.